Food safety in canteens: a public health programme in Aveiro region (Portugal) in 2018 and 2019. (30th September 2020) - Sá, R; Pinho-Bandeira, T; Queiroz, G; Ferreira, D; Lopes, P; Leitão, R; Pedroso, M J
Abstract: Background: Each year, 23 million people get ill from unsafe food in Europe. Food safety refers to the absence or safe acceptable levels of hazards in food that may harm the health of consumers. The Public Health Unit of Baixo Vouga Primary Healthcare Cluster (Aveiro region) developed a programme to identify hazards and promote implementation of corrective measures in community canteens that serve children and elderly. It has three fields of action: qualitative evaluation of the installation and operating conditions, based on the legislation; microbiological surveillance of food and utensils; training of food handlers and managers. This study aims to describe the results of such programme in 2018 and 2019. Methods: This cross-sectional study used data from qualitative evaluation and microbiological results for a descriptive analysis. Additionally, an assess of the compliance of the critical points was performed to identify the main barriers in achieving the proposed targets. Results: From a total of 420 registered canteens, 211 and 294 were evaluated in 2018 and 2019, respectively. For these years, only 87 (41.2%) and 124 (33.3%) fully complied with all critical points. The main problems were the lack of non-manual activation system in wash basins and faucets and inadequately instructed food handlers about required hygiene measures. Microbiological surveillance results of 371 and 393 samples had a proportion of satisfactory or acceptable results of: 93.5% and 91.3% for the main dish; 56.1% and 46.6% for the salads and 82.4% and 79.8% for the utensils. Coliform bacteria were the most common agent. Conclusions: The compliances with critical points were low, accounting for the fact they are legislation-based. The microbiological results were worst for the salads' samples. Deviations give us hints of what should be reinforced. Education of the food handlers and consulting with companies to improve procedures and equipment could be of great use. Key messages: Community canteens' compliances with legislated criteria were low. This programme is useful in identifying vulnerabilities and may lead to the implementation of corrective measures.